Informed consent: some current considerations - Cañete, Roberto; Guilhem, Dirce; Brito, Katia (Acta Bioethica, 2012)
Informed consent constitutes a crucial link in research involving human beings. Nevertheless, knowledge limitations which lead to errors of its process and application have been frequently identified by professionals globally. Hence, a brief review of the topic is exposed about the concept and the elements related to adequate process and application, which we belief will allow to clarify the information that professionals who do research involving human beings posses.